Psycho-social factors determining success in high performance triathlon: compared perception in the coach-athlete pair - Ruiz Tendero, G.; Salinero Martin, J. J. (Perceptual and Motor Skills, 2012)
High level sport can be analyzed using the complex system model, in which performance is constrained by many factors. Coaches' and athletes' perceptions of important positive and negative factors affecting performance were compared. Participants were 48 high-level international triathletes and their coaches (n = 14). They were personally interviewed via a questionnaire designed by four accredited experts, who selected groups of both positive and negative factors affecting performance. A list of factors was developed, in order of greater to lesser importance in the opinion of athletes and coaches, for subsequent analysis. Two ranked lists (positive and negative factors) indicated that athletes appear to rate personal environment factors (family, teammates, lack of support from relatives) higher, while the coaches tended to give more importance to technical and institutional aspects (institutional support, coach, medical support). There was complete agreement between coaches and triathletes about the top five positive factors. Negative factor agreement was somewhat lower (agreement on 3/5 factors). The most important positive factor for coaches and athletes was "dedication/engagement," while the most important factor adversely affecting performance was "injuries."